1999
DOI: 10.1007/bf02235052
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte elastase and systemic cytokine response after laparoscopic-assisted and open resections in Crohn's disease

Abstract: Serum IL-6 and IL-10 may not be ideal measures for evaluation of the degree of tissue trauma in laparoscopic-assisted and open resections in Crohn's disease, probably because of interference with disease-specific cytokine interactions. In contrast, granulocyte elastase has to be considered a strong marker discriminating the different severity of surgical trauma induced by laparoscopic-assisted vs. open resection in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…However, some authors have reported no evidence of improved cell-mediated immunity after laparoscopy [34,35,61]. Discrepancies like these underscore the multifactorial nature of systemic cell-mediated immunity and, perhaps, reflect the tender balance of an immune response only partially measured.…”
Section: Cell-mediated Immunitymentioning
confidence: 88%
“…However, some authors have reported no evidence of improved cell-mediated immunity after laparoscopy [34,35,61]. Discrepancies like these underscore the multifactorial nature of systemic cell-mediated immunity and, perhaps, reflect the tender balance of an immune response only partially measured.…”
Section: Cell-mediated Immunitymentioning
confidence: 88%
“…Its role in surgical trauma has rarely been investigated [15]. Hypothetically, an increase in serum IL-10 levels might reflect the compensation of the surgical trauma-related inflammatory response and the initiation of the healing process.…”
mentioning
confidence: 99%
“…Patients with carcinoma/adenoma were randomly picked for either surgical procedure. Patients with Crohn's disease were randomly distributed to either surgical procedure in the Crohn's Disease Activity Index (CDAI) [14,15], gender, duration of disease, and the like. The result was homogeneous groups (CDAI mean: open, 232.4; laparoscopic, 239.7).…”
mentioning
confidence: 99%
“…However, some authors have reported no evidence of improved immunity after laparoscopy. [8][9][10][11] In addition, port site metastases (PSM) and local recurrences, although occasionally observed, remain a disputable problem with laparoscopic surgery for cancer. 12,13 With respect to renal cell carcinoma (RCC), laparoscopy related studies on the host immunity are insufficient and incomplete.…”
mentioning
confidence: 99%